Das Landesarchiv Schleswig-Holstein. Eine Betrachtung aus archivtechnischer Sicht - Lucht, Roland (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2014)
The Landesarchiv Schleswig-Holstein Schleswig-Holstein is situated in the Prinzenpalais in Schleswig. The Archive is a safe place for the permanent storage of historical and personal historical sources. It also embodies the "public memory" of the northernmost state: with its approximately 10,000 records, 90,000 maps and 38,000 meters of documents, it is the place where major written sources have been permanently secured since the 11th century. The earliest document dates back to 1059. All this makes the Landesarchiv Schleswig-Holstein Schleswig-Holstein a centre of historical, home and family research. Moreover, the preservation of legally binding documents ensures legal certainty for citizens as well as the continuity of the administrative action. The Landesarchiv provides numerous services for Schleswig-Holstein administration, for example investigations for legal or historical purposes, the submission of files or the preparation of expert opinions. The present work of Roland Lucht explores the Landesarchiv from an an archival perspective. This is a completely revised edition.